Narcissist Traits and Transfiguration of Domestic Territory in Anne Tyler's “Saint Maybe” - Tamilmani, Kulamangalam Thiagarajan; Thillainayaki, Sankaranpillai Aruljothi (English Studies at NBU, 2024)
Men and women in the domestic territory are predominantly presented as the main sources of family in most of the contemporary American novels. Yet their significance is portrayed with multitudes of familial responsibilities in nurturing their children. Anne Tyler’s Saint Maybe appraises the familiar theme of ordinary people and their encounter with sufferings to culminate in transfiguration of domestic territory. This paper displays the outlook of ordinary people in Saint Maybe to prevent them from falling astray. More crucially, the framework of the paper lays its emphasis on how Ian Bedloe sheds his narcissistic traits to capture the attention of his brother’s children in the domestic sphere after the death of their parents. Therefore, this paper purports to bring out the effect of narcissistic traits in which Tyler has ingrained a real and a fervent tone about religion to protect Ian Bedloe as a surrogate father.